The Scientific American brave new brain - Horstman, Judith. (Jossey-Bass, 2010)
Judith Horstman presents a highly informative and entertaining look at the future of your brain, based on articles from Scientific American and Scientific American Mind magazines, and the work of today's visionary neuroscientists. --from publisher description